2010
DOI: 10.1128/aac.00746-10
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antifungal Susceptibilities and Amplified Fragment Length Polymorphism Genotyping of a Worldwide Collection of 350 Clinical, Veterinary, and Environmental Cryptococcus gattii Isolates

Abstract: The in vitro susceptibilities of a worldwide collection of 350 Cryptococcus gattii isolates to seven antifungal drugs, including the new triazole isavuconazole, were tested. With amplified fragment length polymorphism (AFLP) fingerprinting, human, veterinary, and environmental C. gattii isolates were subdivided into seven AFLP genotypes, including the interspecies hybrids AFLP8 and AFLP9. The majority of clinical isolates (n ‫؍‬ 215) comprised genotypes AFLP4 (n ‫؍‬ 76) and AFLP6 (n ‫؍‬ 103). The clinical AFLP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
117
3
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(132 citation statements)
references
References 32 publications
9
117
3
3
Order By: Relevance
“…The majority of studies addressing in vitro susceptibility testing for amphotericin B against C. neoformans and C. gattii have shown that many of these isolates are susceptible at MIC values ≤ 1 mg/L [47,48,[50][51][52][53], similar to the MIC values obtained in this work. However, the literature reports MIC values for amphotericin B ≥ 1 µg/mL, such as Lozano-Chui et al [31], who reported MIC values of 3-4 mg/L, which were associated with treatment failure.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The majority of studies addressing in vitro susceptibility testing for amphotericin B against C. neoformans and C. gattii have shown that many of these isolates are susceptible at MIC values ≤ 1 mg/L [47,48,[50][51][52][53], similar to the MIC values obtained in this work. However, the literature reports MIC values for amphotericin B ≥ 1 µg/mL, such as Lozano-Chui et al [31], who reported MIC values of 3-4 mg/L, which were associated with treatment failure.…”
Section: Discussionsupporting
confidence: 75%
“…Following their analysis of susceptibility profiles of C. gattii genotypes, Chong et al [49] reported higher MIC values for fluconazole (≥ 64 µg/mL) against C. gattii VGII than against C. gattii VGIII and VGI [48]. Iqbal et al [50] reported differences in the susceptibility profiles of the molecular types of C. gattii, having determined higher MIC values for the VGII subtypes than the VGI and VGIII subtypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of a number of studies have suggested that differences in in vitro drug susceptibility are correlated with different Cryptococcus species and molecular types (19)(20)(21)(22)(23). MICs of all azoles, particularly fluconazole, appear to be higher for molecular type VGII isolates than for other C. gattii molecular types, primarily VGI, and C. neoformans (19,21,23).…”
mentioning
confidence: 95%
“…MICs of all azoles, particularly fluconazole, appear to be higher for molecular type VGII isolates than for other C. gattii molecular types, primarily VGI, and C. neoformans (19,21,23). There is also growing evidence that antifungal drug susceptibility may vary between geographical locations for the same molecular type (19,21,24).…”
mentioning
confidence: 97%